The Merchant of Venice: Codicia, Traición y Carne. - Baselga Calvo, Mariano (Babel – AFIAL : Aspectos de Filoloxía Inglesa e Alemá, 2019)
The riddle of the caskets in The Merchant of Venice doubtlessly constitutes the central argument of the plot. However, a superficial reading might just give us part of its relevance, for the moral issues behind it are far more ambiguous than they seem. Actually, a deeper view into the behaviour of Portia and Bassanio shows that these apparently ’good characters’ are in fact breaking the Dead Father’ s ’deal’ to obtain mere gain and pleasures of the flesh. So, if Greed, Treachery and Flesh can be seen as the means and motives on Portia and Bassanio’s side, a symmetrical comparison could be established with Shylock and Bassanio’s (the latter having betrayed Antonio’ s friendship ), because treachery has been accomplished on both sides and so has the ’bestowal of flesh’ (or nearly). The peculiarity of the play is that the structural symmetry leads to a dissymmetrical ending: Antonio’ s flesh is not bestowed to the greedy Jew after all. Probably, Shakespeare tumed a tragedy into a comedy to avoid ’shaking the scenes’ once more.